Thermodynamic Study of Formation of the Complexes of Thorium(IV) with Xylenol Orange at Different Temperatures - Kiani, Farhoush; Sharifi, Sasan; Ali Rostami, Abbas; Hagiaghajani, Saeid (Asian Journal of Chemistry, 2010)
The stability constants of the complexes of thorium(IV) ion with xylenol orange were determined in aqueous solution at 15, 20, 25, 30, 35 ºC and also 0.1 mol dm-3 ionic medium using a combination of potentiometric and spectrophotometric techniques. Sodium perchlorate was used to maintain the ionic strength. The composition of the formed complexes was determined and shown that thorium(IV) forms two mononuclear 1:1 species with the ligands, of the type Th(XO) and ThH2(XO)2 in the pH range of 2-6. The logarithms of the cumulative stability constants, βxyz, of the complexes, [(Metal ion)x (H+)y(ligand)z], are log β111 and log β122 : 8.58, 8.13, 7.89, 7.64, 7.42 and 17.09, 16.84, 16.64, 16.49, 16.33 at 15, 20, 25, 30 and 35 ºC, respectively. Some thermodynamic parameters were also calculated at different temperatures. ΔG, ΔH and ΔS values were obtained -19.636 KJ mol-1, -42.622 KJ mol-1 and -77.095 J mol-1 k-1 for ThH(XO) and -41.330 KJ mol-1, -27.768 KJ mol-1 and 45.486 J mol-1 k-1 for ThH2(XO)2 at temperatures were related, respectively.